Bravo! Using Library Dance Collections to Recreate Historical Ballets. Issue 2 (2nd April 2016) - Weiss-Randall, Debra
ABSTRACT: Recreating a kinesthetic art form is not easy. For ballets created in the modern age, film, videotape, and dance notation aid in the reconstruction. For historic masterworks, the process is akin to a detective story, as the dance reconstructors hunt for clues to the missing information. They comb through notated dance and music scores, choreographers' notes, pictures, libretti, reviews, sketches, and eyewitness accounts. These archival materials are commonly housed in libraries' special collections. The Jerome Robbins Dance Collection at the New York City Public Library for the Performing Arts is the foremost collection in the United States, but there are many other excellent collections, including at the Library of Congress and in university libraries. The authors explore one of the great reconstructions of the 20th century—Robert Joffrey's remarkable 16-year effort to recreate Nijinsky's lost choreography for the 1913 ballet The Rite of Spring .